Clinical Profile on Keratoconus Presenting at A Tertiary Eye Care Centre- Tilganga Institute of Ophthalmology - Rana, Rachana Singh; Bajracharya, Leena; Gurung, Reeta (Nepalese Journal of Ophthalmology, 2019)
Introduction: Keratoconus (KC), is a bilateral, noninflammatory degenerative disease of the cornea which is characterized by progressive corneal ectasia and loss of visual function. The onset of KC is commonly seen at puberty and affects approximately 1 in 2000 in the general population. Objective: The aim of this study was to assess the clinical profile of keratoconus in the tertiary eye centre in Nepal. Material and methods: It is a retrospective, hospital based, consecutive study from June 2017 to May 2018. A total of 66 patients (114 eyes) were diagnosed cases of Keratoconus presented in Cornea clinic of Tilganga institute of Ophthalmology. Parameters investigated included patients’ demography, keratometric readings, visualacuity and manifest refraction. Classification of keratoconus was based on Amslern-Krumeich grading system (modified). Results: The mean age of subjects was 18.73 (range: 10-65). Male/female distribution was 48 (72.7%) and 18 (27.3%) respectively. 48 (72.7%) had bilateral keratoconus and 18 (27.3%) were unilateral. Mean Uncorrected visual acuity (UCVA) was 0.80 (range: 0.01-1.00), mean visual acuity ( VA) with spectacle correction was 0.47 (range: 0.01-1.00). Mean spherical amount of refractive was –2.17 (range: −0.50 to −17.00D) and mean cylindrical amount of refraction was -2.85 (range: 0.00 to −6.00). Mean spherical equivalent (SE) of refraction was −4.26 (range: −0.50 to −22.50D). Mean flattest keratometric reading (K1) was 49.63 (range: 40.63-76.70D) and mean steepest keratometric reading (K2) was 53.14 (range: 41.63-73.21D). Mean average keratometric reading was 51.43 (range: 41.63-72.10D). Regarding disease severity, 35.68% of subjects were classified as mild keratoconus, 29.73% as moderate keratoconus, 9.73% as advance keratoconus, while 24.86% were found with the severestage of keratoconus. 78.9% of total eyes presented with minimum pachymetry of 401 to 500 mm. Conclusion: Clinical profile of Nepalese keratoconus patients looks similar to that reported earlier worldwide. The condition was found to manifest at a younger age and was more common in males.